Embodiment as an Instrument for Empathy in Social Work. Issue 2 (3rd April 2021) - van Rhyn, Brianne; Barwick, Alex; Donelly, Michelle
ABSTRACT: It is within and through the body that we experience the physical, social, and emotional dimensions of life. This view draws on the existential phenomenological principal of embodiment, as described by French philosopher Maurice Merleau-Ponty. Empathy is considered essential in the social work professional encounter. Prevailing conceptualisations of empathy in social work rely on simulation theory, where the social worker is expected to emulate the internal emotional and mental state of the client. Phenomenologists question the ontological plausibility of this conceptualisation. Their principal critiques are of mirroring, perspective-taking, and the associated emotional and intellectual labour. Expanding on phenomenological research, we suggest an alternate conceptualisation of empathy that integrates embodiment in social work theory, education, and practice. An embodied approach entails an interpretivist lens of subjectivity, direct perception of another's emotional state, sensitively and bodily attending to narrative, and adopting a compassionate stance of both "understanding and not understanding". IMPLICATIONS: Empathy is an emotion-driven construct. Current views of empathy in social work rely on mentally simulating clients' emotions. Emotions are embodied in that they are physically felt and expressed. The body is therefore a powerful instrument for better understanding and empathising with clients. Future conceptualisations of empathy used in social work theory, education, and practice would benefit from taking an embodied approach.